The Impact of Robotic Process Automation (RPA) on Internal Controls Systems and Audit - Habinshuti, Jean Bertrand; Svatá, Vlasta, 1952-; Zbořil, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
The rise of Robotic Process Automation or RPA across organizations is eminent in this era. Across the globe, enterprises are adopting implementation of Robotic Process Automation technology on top of their existing infrastructure to create software robot often referred to as “bot” capable of executing various business processes just like humans would do. The bot is capable of working 24/7, performing the tasks fast without making any mistakes and the implementation costs are usually less than the cost of an employee, hence fast return on investment for organizations.The business processes relevant for Robotic Process Automation are those which are characterised by a high volume of transactions, where the tasks are repeatable, and rules driven. Susceptibility to automation using RPA technology varies from industry to industry but in most cases back office processes and call centre processes seem to be benefiting from this technology more than any other type of processes. For instance, RPA technology is being used in finance department for automating invoice processing processes, in accounting department for accounting reconciliation processes. The main goal of this thesis is to conduct a research on how audit department can leverage the opportunity brought by Robotic Process Automation technology to increase efficiency and effectiveness of internal audit activities. Furthermore, as organisations embarks on automation initiatives within business processes and functions, it is very likely that their risk profile will be impacted. Internal audit expertise will be needed to address the challenges that the shift to automation will bring. Internal auditor should act as key automation advisor, with a primary focus on assessing the impact of automation initiatives on systems and controls to address the organization’s changing risk profile.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses